Solidarische Care-Ökonomie: Revolutionäre Realpolitik für Care und Klima. - Winker, Gabriele (Xtexte., 2021)
Care work is a vital foundation of society. Without the many people who look after children every day, care for relatives in need of support or help people in crisis, this society would collapse immediately. At the same time, those who take on this work are equally overstretched as the ecosystems and their material cycles on which all life is based. These problems are ultimately not solvable in a capitalist social order. Therefore, we need to radically limit profit-oriented economic activity in favour of a care economy that is oriented towards successful care relationships and the resilience of ecosystems. The concept of the Care Revolution opens the way to a society characterised by care and solidarity instead of competition and exclusion.